The Multifaceted Nature of Clopidogrel Resistance: Integrating Pharmacodynamic, Pharmacokinetic, and Pharmacogenomic - Andika Yusuf Ramadhan (PT Dexa Medica, 2025)
Clopidogrel is a second-generation thienopyridine drug that acts as a platelet aggregation agent and widely used to treat cardiovascular disease by preventing the formation of thrombus. Growing studies in the cardiovascular field have led to a new term, which is clopidogrel resistance. The mechanism of clopidogrel resistance could be the consequence of several factors such as decreased bioavailability due to pharmacokinetic changes, PK/PD interactions with other drugs, and genetic polymorphisms. Genetic polymorphisms affect the metabolism of clopidogrel prodrug, leading to sub-therapeutic concentrations of active metabolites. In addition, mutations in the P2Y12 receptor gene also impact platelet activity against agonis and antagonist ADP. Measurement of platelet activity and pharmacogenomics profiling could help in diagnosing and monitoring clopidogrel therapy with suspicion of clopidogrel resistance.